The Organizational Excellence as Mediation in The Impact of Enterprise Resource Planning and Entrepreneurial Orientation on Organizational Performance - Julya Nada, Elsa; Nurul Qomari, Ika; Fauziyah; Amaripuja, Punang (Business Innovation Management and Entrepreneurship Journal (BIMANTARA), 2026)
Organizational excellence plays a significant role in organizational development, given the role of organizations in the modern world. An organization's ability to adapt and adjust to changes and organizational dynamics plays a crucial role in improving organizational performance. This study focuses on the mediating role of organizational excellence (OXEL) in improving organizational performance (OP) with the exogenous variables of enterprise resource planning (ERP) and entrepreneurial orientation (ENTO) with the object of business organizations in Yogyakarta, Indonesia. Using a quantitative approach with structural equation modelling, this study aims to analyze both the direct and indirect effects of ERP and ENTO on OP through the mediating mechanism of OXEL. This study contributes to strategic management literature and provides practical insights for organizational leaders, policymakers, and business support service providers in enhancing the competitiveness and sustainable growth of organizations in developing countries. The study results indicate that of the seven proposed hypotheses, five are accepted while two are rejected. A detailed discussion is presented in the discussion section. The research findings reveal that entrepreneurial orientation does not influence organizational performance in small business organizations. Similarly, organizational excellence does not mediate the effect of enterprise resource planning on organizational performance